(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The problem of teaching computer science in secondary schools is considered. The need to find and develop new ways and means of filling the learning material related branches of knowledge, the use of elements of a synergistic approach to the planning of the learning process and its activation is highlighted.